MENERAPKAN METODE WEIGHTED PRODUCT (WP) DALAM MENETUKAN SISWA BERPRESTASI (Study Kasus SMK Tarbiyatunnasyiin) - Bahri, Saiful; Imam Agung, Achmad; Sucipto, Hadi (Inovate, 2022)
Tarbiyatunnasiin Vocational School annually holds the selection of high-achieving student scholarship programs, namely students who have achieved high performance in accordance with specified criteria. There are several criteria that are assessed in the selection of high achieving students namely, Mathematics, B.Indonesian, B. English, ICT, religion, discipline, neatness. The purpose of this study is to design a decision support system for Tarbiyatunasiin Vocational School and for the implementation of a decision support system using the Weighted Product (WP) method as a method for selecting high achieving students. WP is one of the methods used in making a decision support system. The results of this study are the decision support system for the selection of outstanding students with several menu options to make it easier for administrators to operate and be able to manage data based on criteria in the process of assessing outstanding students, and the accuracy of valid data in the application of the selection system for SMK Tarbiyatunnasiin Islamic Boarding School students Weighted Product (WP) method is 99.87%. Keywords: Students Achivement, Information systems, WP, Action Research, Website